PROGRESIVITAS PENGELOLAAN DAN PENGEMBANGAN WAKAF UANG DI INDONESIA - sudirman etihed; Zainab Zainab (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2023)
In comparison to other Islamic nations, Indonesia has a very high cash waqf potential because the majority of its citizens are Muslims. Waqf is a way of goodness in Islam and has numerous virtues, hence it has a huge potential for growth. Indonesians are still competing to donate their best assets for waqf for both social and religious reasons. The large potential of the waqf must be followed by good management and development as well. This research uses descriptive analytical method with a qualitative approach. The findings of this study indicate that the potential for cash waqf will continue to increase along with the number of Indonesian Muslim population which is estimated to reach 237.56 million people, and to maximize the potential for cash waqf can be done by investing waqf funds in LKS products and/or Islamic financial instruments . Then the distribution of the profits from the cash waqf will be distributed toexcuse me This can be done with direct community development and empowerment programs managed by Nazhir waqf. or it can also be distribution of profits from cash waqf investments by carrying out community development and empowerment programs through partnerships with other empowerment institutions that meet institutional and professional eligibility criteriaKeywords : Cash Waqf, Nazhir, Development